Preoperative albumin can predict the risk of postoperative deep venous thrombosis in non-cardiac surgery - Shiyan Zhang; Qianyun Pang; Wenjun Liu; Zhu Chen; Ying Wang; Yongting Duan; Hongliang Liu (Frontiers in Medicine)
BackgroundPostoperative deep venous thrombosis (DVT) is a critical complication of non-cardiac surgery. Hypoalbuminemia reflects both nutritional depletion and inflammation, which may contribute to DVT pathogenesis. In this study, we evaluated preoperative albumin’s association with DVT in patients undergoing elective non-cardiac surgery, and identified risk-stratifying thresholds.MethodsA retrospective cohort study was conducted involving 2,026 adult patients (exclude local anesthesia cases) undergoing elective non-cardiac surgeries between December 1, 2023, and December 30, 2024. All patients received standardized postoperative surveillance by bilateral lower limb Doppler ultrasound during hospitalization. The primary exposure was preoperative serum albumin level, the primary outcome was postoperative DVT. Multivariable logistic regression was used to analyze the independent risk factors for postoperative DVT, and assess the prediction of preoperative albumin level.ResultsMultivariable logistic regression revealed five independent risk factors for postoperative DVT (preoperative albumin, age, gender, surgical duration, and Caprini score). A linear dose-response relationship was observed between preoperative albumin levels and postoperative DVT incidence from a linear logistic regression. Each 1 g/L decrement in preoperative albumin level increased the risk of postoperative DVT by 8.8% (adjusted OR (aOR): 1.088, 95%CI: 1.028–1.152) when analyzed as a continuous variable. The optimal preoperative albumin cut-off value was 41.9 g/L to predict the risk of postoperative DVT (aOR:2.169, 95% CI:1.144–4.115), and the AUC was 0.885.ConclusionPreoperative albumin (the cutoff is 41.9 g/L) may help stratify DVT risk in intermediate-risk non-cardiac surgical patients, though prospective validation is needed given study limitations.